1991
DOI: 10.1111/j.1532-5415.1991.tb04450.x
|View full text |Cite
|
Sign up to set email alerts
|

Fever Response in Elderly Nursing Home Residents: Are the Older Truly Colder?

Abstract: Objective To test the hypothesis that many nursing home residents with an apparently blunted fever response (maximum temperature Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 29 publications
(35 reference statements)
5
95
0
1
Order By: Relevance
“…As specific symptoms are often lacking [9][10][11] the presence of fever, in terms of > 38°C, is often evaluated as a significant symptom of illness and an important reason for taking further action. However, fever in frail NHR has been reported to be lower than traditionally stated [17][18][19]. In addition, the effects on body temperature from medication with paracetamol daily have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…As specific symptoms are often lacking [9][10][11] the presence of fever, in terms of > 38°C, is often evaluated as a significant symptom of illness and an important reason for taking further action. However, fever in frail NHR has been reported to be lower than traditionally stated [17][18][19]. In addition, the effects on body temperature from medication with paracetamol daily have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Örneğin ruptüre olmuş bir aort anevrizması yaşlı hastada acil defekasyon hissine neden olabilir, ya da apandisiti olan yaşlı hastalar sadece artmış defekasyon sıklığı ile başvurabilir. Ciddi akut batın problemi olsa da yaşlı hastalar genellikle afebrildirler (22,23). Hipotansif olması gereken kronik hipertansiyonu bulunan bazı geriatrik hastalarda kan basıncı değerleri yanıltıcı biçimde normal ölçülebilir.…”
Section: Tanı Koymada Güçlüklerunclassified
“…Castle SC & Al (1991) found that, in a nursing home population, baseline body temperatures are approximately 0.5°C below those of a normal young person and that with infection, despite a rise in temperature comparable to that seen in the young, the maximum temperature may be below the traditional definition of fever. However, a temperature of 37.8°C coupled with a decline in functional status is highly indicative of infection in this population.…”
Section: Clinical Presentation Of Infectionsmentioning
confidence: 99%
“…However, a temperature of 37.8°C coupled with a decline in functional status is highly indicative of infection in this population. (Castle SC & Al, 1991) The presence or absence of fever-aside from facilitating or inhibiting the diagnosis of infection-has other implications. The presence of fever (as defined by an oral temperature of 38.3°C) is highly specific for the presence of a serious, usually bacterial, infection (Keating MJ III, & Al, 1984;Wasserman M & Al, 1989).…”
Section: Clinical Presentation Of Infectionsmentioning
confidence: 99%